2006
DOI: 10.1128/iai.01215-05
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation among Isolates of Sarcocystis neurona , the Agent of Protozoal Myeloencephalitis, as Revealed by Amplified Fragment Length Polymorphism Markers

Abstract: Sarcocystis neurona causes serious neurological disease in horses and other vertebrates in the Americas. Based on epidemiological data, this parasite has recently emerged. Here, the genetic diversity of Sarcocystis neurona was evaluated using the amplified fragment length polymorphism (AFLP) method. Fifteen S. neurona taxa from different regions collected over the last 10 years were used; six isolates were from clinically diseased horses, eight isolates were from wild-caught opossums (Didelphis virginiana), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
1
7
0
2
Order By: Relevance
“…Previous studies have concluded that S. neurona possesses an intermediate population structure that exhibits both clonal propagation and recombination (Asmundsson et al, 2006; Elsheikha et al, 2006; Sundar et al, 2008). Analysis of markers in the current study supports these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have concluded that S. neurona possesses an intermediate population structure that exhibits both clonal propagation and recombination (Asmundsson et al, 2006; Elsheikha et al, 2006; Sundar et al, 2008). Analysis of markers in the current study supports these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The initial efforts to generate nucleic acid sequence data for S. neurona were conducted in the context of phylogenetic analyses, development of diagnostic probes, and included the use of RAPD assays and sequence analysis of the 18S rRNA locus (Fenger et al, 1994; Granstrom et al, 1994; Dame et al, 1995; Marsh et al, 1999; Tanhauser et al, 1999a, b; Elsheikha et al, 2005a; Elsheikha et al, 2005b; Elsheikha et al, 2006a; Elsheikha et al, 2006b; Elsheikha and Mansfield, 2007; Elsheikha, 2009) to identify species-specific genetic markers. Some of these investigations led to PCR-based tests that detect S. neurona and/or distinguish it from other closely-related species (Fenger et al, 1995; Tanhauser et al, 1999a, b).…”
Section: In Vitro Cultivation Cell and Molecular Biologymentioning
confidence: 99%
“…[45][46][47] However, efforts to increase stress by use of a second transport and treatment with immunosuppressive steroids did not exacerbate disease, 48,49 so it is apparent that the interplay between immune suppression and infection is more complex than currently understood. Modest genetic and antigenic diversity exist among strains of S neurona that have been isolated, [50][51][52] and there is some suggestion that particular parasite genotypes may be more virulent than others. 53 This finding was Equine Protozoal Myeloencephalitis based on a large collection of S neurona isolates from marine mammals, however, and the association between parasite genotype and disease was not apparent in the more limited sample set of isolates from horses suffering from EPM.…”
Section: Pathogenesismentioning
confidence: 97%